Pancreas Divisum as a Rare Etiology of Recurrent Pancreatitis: A Rare Case Ever Documented and Reported In Indonesia - Muhammad Begawan Bestari; Eka Surya Nugraha; Siti Aminah Abdurachman (Acta Medica Indonesiana, 2022)
Pancreas divisum is an abnormal condition of pancreas duct that occurs from organogenesis. This abnormal condition defined as a failure in fusion between dorsal and ventral part of the pancreas. The incidence reported 4%-14% in general population. Majority patient with pancreas divisum will not present with any sign or symptom, but in some cases may present with signs of pancreatitis. We illustrate a case of 39 years old male with pancreas divisum presenting as acute recurrent pancreatitis. Diagnosis of pancreas divisum was determined through magnetic resonance cholangiopancreatography (MRCP) and endoscopic retrograde cholangiopancreatography (ERCP). Patient treated by sphincterotomy and dilation using Soehendra’s dilator catheter. This is the first pancreas divisum case successfully treated and reported in Indonesia.